Impact of the COVID-19 pandemic on voluntary terminations of pregnancy in an Italian metropolitan area. (2nd January 2022) - Guzzetti, Sara; Massarotti, Claudia; Gazzo, Rossella; Paolucci, Roberta; Vallerino, Gabriele; Sirito, Rodolfo; Anserini, Paola; Cagnacci, Angelo
Abstract: Purpose: The COVID-19 pandemic and national lockdown from 9 March to 4 May 2020 changed social, familial, and sexual relationships, as well as how citizens interact with the health services. How these profound changes have affected sexuality, contraception and voluntary terminations of pregnancy is still largely undescribed. The main objective of this study was therefore to find out whether the COVID-19 pandemic and ensuing lockdown affected the demand for legal abortion. Material and methods: The study period was divided into three phases: the pre-pandemic (January and February 2020); lockdown (March and April); and post-lockdown (May and June). The number and characteristics of women requesting pregnancy termination each month during that time were compared with the stats for the same months in the preceding three years (2017–2019). Results: Immediately after national lockdown, the number of voluntary abortions markedly declined (-40.45%). The effect was more evident in women below 20 years of age (-66.67%), employed versus unemployed women (-42.71% vs. −21.05), and non-Italian versus Italian citizens (-53.01 vs. −32.85). No difference was found in the mean time from request to execution of the procedure, or in the type of the procedure used. Conclusion(s): National lockdown reduced the number of unwanted pregnancies, especially in younger women. The Italian health service's response to the demand appears to have been unaffected by the pandemic. However, as the demand for abortion is still high, probably due to unplanned pregnancies among cohabitants within a stable relationship, contraception guidance should be improved among women traditionally deemed low-risk in terms of sexual behaviour.